Preclinical evaluation of AL-001, a gene therapy for wet age-related macular degeneration - Xuan Liu; Haiyan Liu; Lei Wang; Julia Zhao; Xingwang Xie; Long Jiang; Chunlin Adam Zhao (Frontiers in Genetics, 2026)
Background Frequent intravitreal administration of antivascular endothelial growth factor Vascular endothelial growth factor agents remains a major limitation in the management of wet age-related macular degeneration (wAMD). This study evaluated whether suprachoroidal delivery of an engineered recombinant adeno-associated viral (rAAV)-aflibercept vector could achieve sustained, targeted expression with improved efficacy and safety compared with intravitreal administration. Methods AL-001, an engineered rAAV vector expressing aflibercept, was developed and characterized. Its expression profile was first assessed in New Zealand white rabbits following suprachoroidal space (SCS) injection. Efficacy, pharmacokinetics, and safety were then evaluated in a nonhuman primate model of laser-induced choroidal neovascularization (CNV), comparing SCS and intravitreal (IVT) administration routes. Results AL-001 efficiently expressed aflibercept in relevant ocular cells in vitro . In rabbits, SCS administration produced sustained aflibercept levels in ocular tissues. In the nonhuman primate CNV model, a single SCS injection of AL-001 showed favorable efficacy to IVT injection and a notable mild inflammatory response. At week 4, grade IV lesion incidence was 0% (0/48) after SCS administration versus 14.3% (6/42) after IVT administration (absolute difference, −14.3 percentage points; 95% CI, 3.7%–27.8%; P = 0.0258). Throughout follow-up, mean leakage area and grade IV lesion incidence remained 0 with SCS, versus IVT peaks of approximately 0.3 mm 2 and 33.0%, respectively, declining to 0.03 mm 2 and 2.0% by day 100. Both the medium and high doses decreased pathological vascular leakage and subretinal hyperreflective material. Vector administration preceded laser-induced CNV modeling, demonstrating that sustained intraocular aflibercept expression in the retina and choroid provided durable antiangiogenic protection. Pharmacokinetic analysis confirmed distinct ocular exposure profiles between routes, with viral genomes confined predominantly to the injected eye and no significant systemic accumulation. AL-001 was well tolerated, without sustained intraocular pressure elevation or severe ocular inflammation, and only mild-to-moderate treatment-emergent adverse events. Low pre-existing anti-AAV2 immunity and time-dependent neutralizing antibody responses postdosing, informing a translational model for patient stratification and redosing feasibility. Conclusion Suprachoroidal administration of AL-001 is well tolerated and provides durable, targeted aflibercept expression with pronounced antiangiogenic efficacy. These results support AL-001 as a promising, long-acting therapeutic candidate for wAMD.